Layanan Konseling Keluarga Pada Klinik Keluarga Sakinah Pimpinan Daerah Aisyiyah Kota Sinjai - Suryanti Suryanti; Muhammad Ilyas; Suhaimi Suhaimi (Al-Ittizaan: Jurnal Bimbingan Konseling Islam, 2018)
Family Clinics is a community institution of engaged in Family Counseling. Refers to Civil Rights and Political Ordinance in 23 Paragraph 1, which explains that the family is a small unit that is entiled to protection by society and the state of society. The working are organizations such as Family Clinic covers about settling the problems occurred in the family, either the complication of preventive and rehabilitative. Provide to the community, both individuals and families in it has a problem.The purpose of this study was to determine the family counseling service of Sakinah Family Clinic of the region of Aisyiyah movement in Sinjai. The Method used in this research is qualitative research method are conducted intensive studies and detailed in an organization or institution. The data obtained are mostly primary data collected directly from informants, as well as with a there is a source secoundary data. Methods of data collection in this study is to optimize the process of observation, interviews and documentation.Family Counseling Services in family coaching sakinah at Sakinah Family Clinic Aisyiyah Kota Sinjai done very well by putting forward the ethics of counseling also using the islamic approach religious advice that is part of the solution faced by clients, the form of counseling done by the counselor to the client is also no rigid with only face to face but also by optimizing exiting communication tools and the freedom of counselor and client on the determination of time and place in conducting counseling.Kata Kunci : Family Counseling, Sakinah Family